Evaluation of Hybrid Post-Quantum Digital Certificates for Integration into Java Platforms - Farias, Henrique Acacio de Souza; Giron, Alexandre Augusto (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on CybersecurityDO - 10.5753/sbseg_estendido.2025.11849, 2025)
Quantum computing threatens classical cryptography, threatenin current and future data. As post-quantum standards mature, hybrid solutions (combining classical and post-quantum algorithms) are critical for security. This paper analyzes hybrid signature algorithms (ECDSA/Ed25519 + Falcon/Dilithium) for Java-based certificate platforms. We benchmark key generation, signing, and verification performance, proposing an integration with CZERTAINLY, an open certificate management system.